2012
DOI: 10.1371/journal.pone.0044221
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Integration Ameliorates Negative Effects of Drought Stress in the Clonal Herb Fragaria orientalis

Abstract: Clonal growth allows plants to spread horizontally and to establish ramets in sites of contrasting resource status. If ramets remain physiologically integrated, clones in heterogeneous environments can act as cooperative systems – effects of stress on one ramet can be ameliorated by another connected ramet inhabiting benign conditions. But little is known about the effects of patch contrast on physiological integration of clonal plants and no study has addressed its effects on physiological traits like osmolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 84 publications
2
11
0
Order By: Relevance
“…The high clonal integration had been found in previous studies on F. orientalis [ 22 , 30 , 47 ] and other Fragaria species [ 20 , 48 - 50 ]. In this study, clonal integration between the ramets of intact clonal fragments was observed both in reciprocal patchiness and in coincident patchiness by comparison with severed fragments.…”
Section: Discussionsupporting
confidence: 69%
“…The high clonal integration had been found in previous studies on F. orientalis [ 22 , 30 , 47 ] and other Fragaria species [ 20 , 48 - 50 ]. In this study, clonal integration between the ramets of intact clonal fragments was observed both in reciprocal patchiness and in coincident patchiness by comparison with severed fragments.…”
Section: Discussionsupporting
confidence: 69%
“…Clonal integration, the movement of resources or signals between connected ramets within clonal fragments, has been repeatedly shown to increase the performance of clonal plants in heterogeneous environments where connected ramets experience different levels of resource availability (e.g., Alpert and Mooney 1986;Hutchings and Wijesinghe 1997;Xu et al 2010;Zhang et al 2012;Song et al 2013;Touchette et al 2013). By resource, we mean something whose use by one plant precludes its simultaneous use by another, such as light, water, mineral nutrients, CO 2 , or O 2 taken up by plant organs; or physical space used for attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Clonal plants depend on an extensive rhizome-root system, which has the ability to extend through a large area and create many clones. The rhizome acts as a spacer and is an important vascular system for physiological integration of clonal plants [13,14]. The rhizome of moso bamboo (Phyllostachys edulis) acts as a spacer for resource sharing between cloned ramets of P. edulis [15].…”
mentioning
confidence: 99%